2006
DOI: 10.1590/s1519-566x2006000300012
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of leguminous cover crop pollens as food source for the green lacewing Chrysoperla externa (Hagen) (Neuroptera: Chrysopidae)

Abstract: Adequação do Pólen de Leguminosas Utilizadas em Adubação Verde como Fonte de Alimento paraChrysoperla externa (Hagen) (Neuroptera: Chrysopidae) RESUMO ABSTRACT -Diversification of crops with species that provide suitable pollen for predators may reduce pest population on crops by enhancing predator effectiveness. In this paper we evaluated the suitability of leguminous cover crop pollens to the predatory green lacewing Chrysoperla externa (Hagen). The predator is commonly found in coffee agroecosystems and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 29 publications
1
33
0
6
Order By: Relevance
“…The architecture of the stems and dense cultures of C. juncea favored by increased humidity and lower temperature, providing areas of refuge and shelter for parasitoids and predators, besides beneficial mites and nematodes in soil (McSorley et al, 2009). A greater number of Chrysoperla externa (Neuroptera: Chrysopidae) and higher levels of bee pollination were observed during the flowering period of C. juncea, because its yellow flowers had large amounts of pollen and gave off an attractive smell (Venzon et al, 2006). Natural enemies associated with C. juncea migrated to agricultural crops when the plants were grown in systems of rotation or succession (Gill et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The architecture of the stems and dense cultures of C. juncea favored by increased humidity and lower temperature, providing areas of refuge and shelter for parasitoids and predators, besides beneficial mites and nematodes in soil (McSorley et al, 2009). A greater number of Chrysoperla externa (Neuroptera: Chrysopidae) and higher levels of bee pollination were observed during the flowering period of C. juncea, because its yellow flowers had large amounts of pollen and gave off an attractive smell (Venzon et al, 2006). Natural enemies associated with C. juncea migrated to agricultural crops when the plants were grown in systems of rotation or succession (Gill et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The larvae of Chrysoperla carnea (Stephens) feed on a wide range of small, softbodied arthropods with a preference for aphids (Principi and Canard 1984). Non-prey foods such as honeydew, floral and extrafloral nectar, and pollen can be important resources for chrysopids in both larval (Downes 1974) and adult (Venzon et al 2006) stages. Limburg and Rosenheim (2001) showed that extrafloral nectar was an important food source for neonate lacewing larvae on cotton and that its consumption increased as the availability of aphid prey declined.…”
mentioning
confidence: 99%
“…Agricultural ecosystems with a diversified flora and, consequently, a diversified pollen grain pool, may better promote the control of pests through greater predator efficiency (Venzon et al, 2006). Fitness of adult Chrysopidae depends on imaginal nourishment and pollen provides them with the nutrients necessary for oviposition (fertility) (Sundby, 1967).…”
Section: Discussionmentioning
confidence: 99%